Acute-phase innate immune responses in SIVmac239-infected Mamu-B*08+ Indian rhesus macaques may contribute to the establishment of elite control - Rosen, Brandon C.; Sawatzki, Kaitlin; Ricciardi, Michael J.; Smith, Elise; Golez, Inah; Mauter, Jack T.; Pedreño-López, Núria; Yrizarry-Medina, Aaron; Weisgrau, Kim L.; Vosler, Logan J.; Voigt, Thomas B.; Louw, Johan J.; et al. (Frontiers in Immunology, 2024)
Spontaneous control of chronic-phase HIV/SIV viremia is often associated with the expression of specific MHC class I allotypes. HIV/SIV-specific CD8+ cytotoxic T lymphocytes (CTLs) restricted by these MHC class I allotypes appear to be critical for viremic control. Establishment of the elite controller (EC) phenotype is predictable in SIVmac239-infected Indian rhesus macaques (RMs), with approximately 50% of Mamu-B*08+ RMs and 20% of Mamu-B*17+ RMs becoming ECs. Despite extensive characterization of EC-associated CTLs in HIV/SIV-infected individuals, the precise mechanistic basis of elite control remains unknown. To gain insight into the immunological factors involved in the determination of EC status, we vaccinated 16 Mamu-B*08+ RMs with Vif and Nef to elicit EC-associated CTLs, then subjected these 16 vaccinees and an additional 16 unvaccinated Mamu-B*08+ controls to repeated intrarectal SIVmac239 challenges. Vaccination did not provide protection against acquisition, but peak and setpoint viremia were significantly lower in vaccinees relative to controls. We did not identify any meaningful correlations between vaccine-induced CTL parameters and SIVmac239 acquisition rate or chronic-phase viral loads. Ultimately, 13 of 16 vaccinees (81%) and 7 of 16 controls (44%) became ECs (viremia ≤ 10,000 vRNA copies/mL plasma for ≥ 4 weeks). Because EC and non-EC viral load trajectories begin diverging by day 14 post-infection, we hypothesized that hyperacute innate immune responses may contribute to viremic control. We performed whole-blood transcriptomic analysis of all 32 SIVmac239-infected Mamu-B*08+ RMs and eight SIVmac239infected Mamu-B*08 -RMs during the first 14 days of infection. We identified subsets of immunomodulatory genes differentially expressed (DE) between RM groupings based on vaccination status, EC status, and MHC class I genotype. These DE genes function in multiple innate immune processes, including the complement system, cytokine/chemokine signaling, pattern recognition receptors, and interferon-mediated responses. A striking difference in the kinetics of differential gene expression among our RM groups suggests that Mamu-B*08associated elite control is characterized by a robust, rapid innate immune response that quickly resolves. These findings indicate that, despite the association between MHC class I genotype and elite control, innate immune factors in hyperacute SIV infection preceding CTL response development may facilitate the establishment of the EC phenotype.